Modelling Amazonian forest eddy covariance data: a comparison of big leaf versus sun/shade models for the C-14 tower at Manaus I. Canopy photosynthesis - Mercado, Lina; Lloyd, Jon; Carswell, Fiona; Malhi, Yadvinder; Meir, Patrick; Nobre, Antônio Donato (Acta Amazonica, 2006)
In this study, we concentrate on modelling gross primary productivity using two simple approaches to simulate canopy photosynthesis"big leaf" and "sun/shade" models. Two approaches for calibration are usedscaling up of canopy photosynthetic parameters from the leaf to the canopy level and fitting canopy biochemistry to eddy covariance fluxes. Validation of the models is achieved by using eddy covariance data from the LBA site C14. Comparing the performance of both models we conclude that numerically (in terms of goodness of fit) and qualitatively, (in terms of residual response to different environmental variables) sun/shade does a better job. Compared to the sun/shade model, the big leaf model shows a lower goodness of fit and fails to respond to variations in the diffuse fraction, also having skewed responses to temperature and VPD. The separate treatment of sun and shade leaves in combination with the separation of the incoming light into direct beam and diffuse make sun/shade a strong modelling tool that catches more of the observed variability in canopy fluxes as measured by eddy covariance. In conclusion, the sun/shade approach is a relatively simple and effective tool for modelling photosynthetic carbon uptake that could be easily included in many terrestrial carbon models.
Modelagem de dados de covariância de fluxo turbulento na floresta amazônica: uma comparação entre os modelos "folha-grande" e "sol/sombra" para a torre C-14 em Manaus. I. Fotossíntese do dossel
Keywords: Modelling Canopy Photosynthesis; Reforestation; Amazon; Eddy Covariance; Modelagem Da Fotossíntese No Dossel; Floresta Tropical; Amazônia; Técnica De Covariância De Fluxo Turbulento